Modified Epiblepharon Repair Preserving Orbicularis Oculi Muscle - Hyun Chul Youn; Seunghwan Lee; Ju-Hyang Lee (Journal of Ophthalmology)
Background/Aims. Conventional epiblepharon repair using anterior lamellar debulking can flatten the lower eyelid, which can cause cosmetic problems in Asian individuals, such as tarsal hollowness. This study describes a modified epiblepharon repair which preserves the orbicularis oculi muscle and surgical efficacy in terms of anatomical and cosmetic outcomes. Methods. A retrospective review of was conducted of patients who received modified epiblepharon repair preserving orbicularis oculi muscle from April 2016 to October 2018. Removal of the orbicularis oculi muscle was minimally performed with eyelash rotating sutures and epicanthal weakening procedure. The preoperative severity of epiblepharon was classified according to skin fold height and cilia-corneal touch. Main postoperative outcomes were evaluated by functional success and cosmetic satisfaction. Results. A total of 208 eyelids of 104 patients were evaluated. The mean age was 7.2 ± 4.2 years with a mean follow-up time of 5.6 ± 4.6 months. Functional success was obtained in 206 eyelids (99.0%). Only two cases that had a total epiblepharon score of 7 showed a recurrence of mild cilia-corneal touch, but reoperation was not required. The cosmetic satisfaction score was 8.7 ± 1.8 (range, 1–10). The excellent cosmesis group with a cosmetic score of 9 or higher had significantly higher skin fold height (p=0.027). Conclusions. Modified epiblepharon repair preserving orbicularis oculi muscle can be effective in the treatment of lower epiblepharon regardless of its severity. Excellent outcomes were obtained functionally and cosmetically without debulking of the orbicularis oculi muscle.